Tenacidade à fratura e fragilização por hidrogênio de aços de alta resistência e baixa liga - Melo, Guilherme Freitas (2019)
High strength low alloys steels are commonly used in a variety of equipment and structures in the offshore oil and gas sector. Subsea components and structures are subject to cathodic protection in order to mitigate their corrosion in service, allowing the occurrence of a process called hydrogen embrittlement (HE). In such scenario, the susceptibility to hydrogen embrittlement (SHE) of the materials must be evaluated. By not depending on complex equipment together with the possibility of testing several specimens at the same time, the Double Cantilever Beam (DCB) is an alternative for determining the threshold stress intensity factor (KTH), which is extremely important for the specification of materials for these applications. This test is directly related to Fracture Mechanics and HE. Therefore, after an incubation period, a force applied on the specimen is responsible for nucleating a crack at the root of the notch in a displacement control, made propagating it until the crack propagation rate is approximately zero and therefore, the value of the applied stress intensity factor (KAP) reaches KTH. In this work, two steels (C and F) were tested in air, obtaining the curves J-R with KJIC as well, showing that steel F has its value around 49 % higher than steel C. It was also observed that in the testing DCB with cathodic protection at -1.2 VAg /AgCl, the average KTH was 29.59 MPa.m0.5 for the C steel. However, for the case of the steel F, the test conditions did not provide a nucleation and a sustainable crack growth, resulting in multiple cracks of less than 2.5 mm in length. Therefore, to evaluate the susceptibility of the two steels, new tests were carried out Rising Step Load (RSL), and it was verified the SHE of the F steel by this method, indicating that the DCB tests for this material should be performed in conditions of longer times with forced aqueous media recirculation, pH control and temperature.